1985
DOI: 10.1111/j.1600-0528.1985.tb00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation rate in oral submucous fibrosis over a 17‐year period

Abstract: Sixty-six patients with oral submucous fibrosis were followed-up for a period of 17 yr (median observation 10 yr) in Ernakulam District, Kerala, India. Oral cancer developed in five (7.6%) patients. The malignant transformation rate in the same sample was 4.5% over a 15-yr observation period (median 8 yr). These findings impart a high degree of malignant potential to this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
228
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 329 publications
(233 citation statements)
references
References 1 publication
3
228
2
Order By: Relevance
“…Incidence of malignant transformation of OSMF was found to be 4.23 % in the present study which is significantly higher than few studies carried out in the past, but is in conformity with the studies of Pindborg et al [19] in 1984, whereas less than the incidence found by Murti et al [14] in 1985. Both these studies were carried out in the Indian subcontinent, where betel nut chewing with or without tobacco is commonly seen in the society.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Incidence of malignant transformation of OSMF was found to be 4.23 % in the present study which is significantly higher than few studies carried out in the past, but is in conformity with the studies of Pindborg et al [19] in 1984, whereas less than the incidence found by Murti et al [14] in 1985. Both these studies were carried out in the Indian subcontinent, where betel nut chewing with or without tobacco is commonly seen in the society.…”
Section: Discussionsupporting
confidence: 90%
“…OSMF is also found to be associated with other premalignant lesions [14,19] like leukoplakia and erythroplakia and in the present study the incidence of the same was found to be 11 %. Normally in the OSMF, the oral mucous membrane is found to be severely atrophic and development of such lesions like leukoplakia and erythroplakia associated with acanthosis and proliferation of epithelial lining warrants serious thought and early intervention, as it could be a transition from fibrosis to a frank squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Its precancerous nature was first described by Paymaster [2], who recorded the onset of slowly growing squamous cell carcinomas in one-third of patients with it. Minti et al reported a malignant transformation rate of 7.6% [3].…”
Section: Introductionmentioning
confidence: 99%